High-Throughput Screening Assay In 384-Well Format For The Identification Of Anti-Trypanosomal Agents Against Trypanosoma Brucei Rhodesiense And Mode Of Cell Death Study - Lim, Kah Tee (2017)
In order to accelerate the discovery of novel leads for the treatment of Human African Trypanosomiasis (HAT), it is necessary to have a simple and sensitive assay to identify positive hits by whole cell viability based high-throughput screening (HTS). In this study, the HTS assay was developed in 384-well format using clear plate and black plate, for comparison. Assay robustness and reproducibility were determined under the optimized conditions in 384-well plate was well tolerated in the HTS assay, including percentage of coefficient of variation of 4.68% and 4.74%, signal-to-background ratio of 12.75 and 12.07, and Z’ factor of 0.79 and 0.82 in clear- and black-384-well plate, respectively.